Critical Analysis of Elementary School Students on Water Privatization in Indonesia: A Critical Literacy Education Project - Rengganis, Ira; Ibrahim, Teguh Teguh; Hendriani, Ani; Juwita, Winda Marlina (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2022)
The background of this study is the increasingly massive water privatization project carried out by foreign companies, which triggers the injustice related to water acquisition rights experienced by Indonesians. The aim of this research is to sue water privatization through education based on critical literacy in elementary schools. The students needed to confront problematic texts, which were then critically analyzed to produce new arguments to promote justice, solutions, and hope. The research method used is a case study that aims to have an in-depth understanding of the results of elementary school students' analyses of the water privatization practice. The results of this study conclude that water privatization can be sued in various ways, one of which is by providing critical literacy-based education and socialization aimed at uncovering the facts of injustice from the practice. Through education based on critical literacy, elementary school students are able to parse problems by identifying causality in the text, promoting hopes for justice, and producing argumentative texts that are rival and solutions to water privatization